MODERN TYPES OF FINANCING LARGE INVESTMENT PROJECTS (NUCLEAR POWER PLANT CONSTRUCTION) - А. M. Kryukov (Real Economics Publishing House, 2015)
Large investment projects require raising high volumes of financial resources on the long term. There is a task now set to raise private capital into the power field more actively and to develop state-private partnership. The article analyses modern types of financing: ВОО (Build - Own - Operate) and ВООТ (Build - Own - Operate - Transfer) that allow to accumulate required financial resources, reduce investment risks and combine interests of different parts participating in a project.